Morphology, anatomy and cytology of critically endangered endemic Minuartia nifensis from West Anatolia, Turkey - Gucel, Salih (Universiti Kebangsaan Malaysia, 2013)
Minuartia nifensis Mc Neill belongs to Caryophyllaceae family. It is distributed only on Nif Mountain. In order to prepare the basis for the ex-situ and in-situ protection principles, ecological data was collected as well as population size and distributon areas were recorded in an earlier study. Present study investigates the M. nifensis anatomically, morphologically and cytologically, with the aim of improving the description of this endemic species and establishing the basic information for future biosystematic studies.